Exploration of fabrication methods for planar CH3NH3PbI3 perovskite solar cells. (September 2016) - Kang, Rira; Yeo, Jun-Seok; Lee, Hyeon Jun; Lee, Sehyun; Kang, Minji; Myoung, NoSoung; Yim, Sang-Youp; Oh, Seung-Hwan; Kim, Dong-Yu
Abstract: Solar cells based on organic-inorganic perovskite materials have dramatically developed in just a short period of time because of efficient light absorption and their unique semiconducting nature. The best power conversion efficiency is continuously recorded via various approaches; devices from sensitized mesoporous structures to planar structures, modified composition of perovskite, and fabrication methods. Despite the amazing improvement, many groups have encountered low reproducibility and lower device efficiency than reported results because of the perovskite's own instability and sensitivity under ambient conditions; thus, we need a realistic and experimental investigation. In this study, we compare solution processing representative fabrication methods, which influence the growth, crystal orientation, and the electronic properties of CH3 NH3 PbI3, device reproducibility, and efficiency in planar perovskite solar. This comparative study gives a realistic overview of the fabrication methods for planar perovskite solar cells. Graphical abstract: Highlights: Comparative study of solution processing CH3 NH3 PbI3 fabrication methods. The crystal orientation of CH3 NH3 PbI3, the distribution of device efficiency. A realistic overview of the fabrication methods for planar perovskite solar cells.